Beyond guidelines: A qualitative clinical stakeholder study of optimal management of anterior cruciate ligament rehabilitation. (19th July 2022) - Dunphy, Emma; Button, Kate; Murray, Elizabeth; Hamilton, Fiona L.
Abstract: Aims: This study gathered expert perspectives in the management of anterior cruciate ligament (ACL) rehabilitation to explore current practice, variations in care and optimal management strategies. Materials and methods: This was a qualitative semi‐structured interview study. The participants' experiences were considered in terms of their roles as employees, managers, clinicians and professional gatekeepers. Purposive and snowball sampling were used to recruit physiotherapists and orthopaedic surgeons. Participants were included if they had a proven record in clinical management or research involving ACL patients. Persons were excluded if they could not speak English. Interviews were conducted in person, via skype or over the phone at a time convenient to the participant. Data was analysed using a framework analysis and critical realist approach. Results: Results included 24 interviews that were conducted with 19 physiotherapists and 5 surgeons. Themes of variation in current care and optimal care were explored including subthemes of patient centred practice, evidence based medicine, resources, self‐management, multidisciplinary teamwork, training and expertise were explored. Participant's perceptions of current care were that it was a location 'lottery' that significantly varied for patients across the UK. Conclusions: Stakeholders identified that optimal management should be patient centred and incorporate adequate equipment, specific training for physiotherapists and a closely communicating multidisciplinary team. Research is needed to explore cost effective models of optimal rehabilitation that include return to sport strategies.